A c(RGDfE) conjugated multi-functional nanomedicine delivery system for targeted pancreatic cancer therapy. Issue 6 (12th December 2014) - Sun, Jing; Kim, Dong-Hyun; Guo, Yang; Teng, Zhaogang; Li, Yanjun; Zheng, Linfeng; Zhang, Zhuoli; Larson, Andrew C.; Lu, Guangming
Abstract : Pancreatic cancer is one of the five most lethal malignancies and has a poor prognosis due to its abundant stromal barriers and lack of effective available therapies. Abstract : Pancreatic cancer is one of the five most lethal malignancies and has a poor prognosis due to its abundant stromal barriers and lack of effective available therapies. Although gemcitabine has been used as a standard therapy for several decades, there has been little progress in the improvement of the 5 year survive rate due to the low targeting efficiency for pancreatic cancer cells. To achieve a targeted delivery of gemcitabine to pancreatic cancer cells, we have developed a c(RGDfE) [cyclic (Arg-Gly-Asp-d -Phe-Glu)] conjugated multi-functional nanomedicine delivery system composed of a magnetic core and mesoporous silica shell. These magnetic mesoporous nanoparticles demonstrated sufficient relaxivity properties for detection with magnetic resonance imaging (MRI). These c(RGDfE) peptide conjugated magnetic mesoporous silica nanoparticles [c(RGDfE)–pMMSNs] can target pancreatic cancer cells and increase cellular uptake in human pancreatic cancer cell lines that overexpress integrin α ν β3 . Gemcitabine loaded c(RGDfE)–pMMSNs were most efficiently targeted to pancreatic cancer cells (BxPC-3). Growth inhibition of the BxPC-3 cell line was achieved in a time dependent manner consistent with observed drug release behavior. Intracellular targeted gemcitabine delivery using c(RGDfE)–pMMSNs offers a promising approach for the treatment of pancreatic cancer.